Comparative Analysis of Space Efficiency in Three Co-Working Spaces in Jakarta - Salim, Nixon; Anshory, Boike Janus; Kurniawan, Rizki (Pendhapa, 2023)
In Indonesia, many companies operate from their own offices, whether in buildings or shop houses. However, co-working spaces have emerged since 2010, providing a viable alternative for entrepreneurs, particularly start-ups, freelancers, and small business owners who lack the capital to lease traditional office spaces. Co-working spaces have seen significant growth, especially in Jakarta, driven by the need for flexible and cost-effective workspace solutions. This research aims to examine the effectiveness of space utilization in co-working spaces in Jakarta, focusing on three specific locations: InHype.Co, UnionSpace, and Ko+labora. By employing both quantitative and qualitative methodologies, including surveys, direct observation, and interviews, this study provides a comprehensive analysis of space efficiency in these co-working environments. The findings reveal key factors that contribute to effective space utilization, including layout design, furniture functionality, and the balance between private and communal areas. The insights from this research are intended to inform entrepreneurs and designers on optimizing co-working spaces to enhance productivity and user satisfaction.